Identification of Laboratory Management Systems at Senior High Schools In Mataram City - Suyantri, Eni; Handayani, Baiq Sri; Lestari, Tri Ayu; Setiawan, Heru (Biota, 2024)
The Laboratory for Biology serves an effective educational facility for learning of biology, where biology subject often requires lab activity. Proper management of the laboratory is a crucial aspect for the smooth execution of practical activites by both teachers and students. The objective of this research was to determine the biology laboratory management system at SMA Negeri 3 Mataram. This research is descriptive research using observation and interview methods. The data collected in two types, the primary data is observation questionnaire and the result of interview to the biology teachers of SMAN 3 Mataram. The development of the observation questionnaire for the standardization of biology laboratory refers to the National Education Minister’s Regulation No. 24 of 2007, and the laboratory management standards refer to The Minister of Education and Culture’s Regulation No.8 of 2018. There are ten aspects considered in the observation of the biology laboratory, including the evaluation of the laboratory space, the completeness of laboratory equipment and materials, and the cleanliness of the laboratory. Based on the research found that eight aspects were categorized as very good, and two aspect were categorized as as good. The completeness of laboratory tools and materials, as well as laboratory safety, need to be improved.